Digital Synergy - Ibrahiem M. M. El Emary; Anna Brzozowska; Piotr Maśloch (CRC Press, 2025)
In an era where technological progress redefines the boundaries of business and management, ‘Digital Synergy - Innovative Management in the ICT Era'emerges as a guide for current and aspiring leaders. This book delves into the heart of modern management practices, illuminated by the transformative power of Information and Communication Technologies (ICT) and digital synergy. Facing the relentless pace of change, adaptation, innovation, and the utilization of digital synergy are no longer optional; they are the bedrock of sustainable success. Through a carefully selected collection of theories, case studies, expert insights, and examples of digital synergy, this book provides the foresight and tools necessary to navigate through the complexities of a globalized, digital marketplace.The book is divided into four sections:1. Financial and strategic management in uncertain times2. Global trends and management challenges3. Corporate social responsibility and effective CSR management4. The future of logistics, with a special focus on military logisticsDesigned for business leaders, managers, students, and anyone keen on deepening their understanding of how ICT and digital synergy shape management strategies, this book is a call to action. It challenges to not just keep pace with technological progress but to lead the charge in leveraging it for strategic advantage.